Four travelogues on the politics of river: water conflict, climate change, and ecocide - Shyam, Kanseng; Bordoloi, Mridul, Bordoloi, Mridul; Diengdoh, Basil N. Darlong (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article critiques the biopolitical and ecocritical aspects of water insecurity and hydro-hegemony, centring river narratives through River Dog, Himalaya, Tales from the River Brahmaputra, and The Braided River. Besides, it examines how environmental negligence, climate change, and geopolitical conflict, especially between India and China, threaten riverine ecologies and vulnerable downstream populations. The Brahmaputra River becomes a contested space where dam-building races, colonial legacies, and ecological violence intersect. Rivers' multifarious roles in the lives of people, especially in the Indian state of Assam, showcase their unprecedented impact on culture, livelihood, ecology, society, religion, identity, and economy. Simultaneously, increasing climate variability pushes the same civilisation to the brink of extinction, as seen in travel narratives related to Dibrugarh town and Majuli river island through erosion, flooding in Assam and Bangladesh, and illegal immigration, which exacerbate land insecurity, identity crises, and political conflict. The fear of Chinese dams in Tibet is linked to small-scale fishermen's precarious livelihoods in Goalpara, Assam, as well as fears of potential weaponisation of dam water downstream. Illegal logging, disappearing river dolphins, death and suffering of animals in Kaziranga National Park, isolated river island communities, and tragedies in river boat transportation highlight the river's role in civilisation survival, water conflict, climate change impacts, and the necessity of ecological and legal remedies in politics. The analyses of travel narratives expose marginalisation through firsthand observations amid global power struggles and argue that recognising ecocide as an international crime could help mitigate rising environmental dangers and ensure trans boundary ecological justice.